“Caracterização hidrogeológica do Sistema Aquífero Bauru na área urbana de Primavera do Leste/MT” - Zimmer, Jefferson Richard (2014)
In this work the hydrogeological characterization of the Bauru Group was held in the urban area of Primavera do Leste, using existing data from wells, geology, morfopedologia and vertical electrical sounding. The Bauru Aquifer System was evaluated using hydraulic conductivity, storage coefficient, static water level, discharge, depth of wells and water quality data. The wells that explotam the Bauru were analyzed in terms of technical structure and geological profile. The results show that, in the area, Bauru is similar hydraulic characteristics to the rest of Brazil, indicating a good production capacity water, as shown the discharge wells. Its waters are acidic, some places have iron content above the VMP, but can be considered potable. The wells less than 10% meet the technical criteria of ABNT, which can is contributing to some local water quality problems such as turbidity, iron, etc. The knowledge and data produced are an essential to support the policy of water management in the city and performing on the sustainable use of these waters educational campaigns tool.